Enhancing bank transparency: A re-assessment - Ari Hyytinen; Tuomas Takalo (Bank of Finland, 2000)
Transparency regulation aims at reducing financial fragility by strengthening market discipline.There are however two elementary properties of banking that may render such regulation inefficient at best and detrimental at worst.First, an extensive financial safety net may eliminate the disciplinary effect of transparency regulation.Second, achieving transparency is costly for banks, as it dilutes their charter values, and hence it also reduces their private costs of risk-taking.We consider both the direct costs of complying with disclosure requirements and the indirect transparency costs stemming from imperfect property rights governing information and specify the conditions under which transparency regulation can (and cannot) reduce financial fragility.
URN:NBN:fi:bof-20140807260
Keywords: 330; information disclosure; market discpline; bank transparency; deposit insurance; financial safety net